2018
DOI: 10.1108/ec-02-2017-0067
|View full text |Cite
|
Sign up to set email alerts
|

A numerical algorithm for computational modelling of coupled advection-diffusion-reaction systems

Abstract: Purpose This paper aims to capture the effective behaviour of nonlinear coupled advection-diffusion-reaction systems and develop a new computational scheme based on differential quadrature method. Design/methodology/approach The developed scheme converts the coupled system into a system of ordinary differential equations. Finally, the obtained system is solved by a four-stage RK4 scheme. Findings The developed scheme helped to capture the different types of patterns of nonlinear time-dependent coupled adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Furthermore, it is demonstrated that the nonuniform grids improve the accuracy of the solution considerably without any extra computational cost (see Table , Figure a,b). The present scheme offered better results than for the linear model, and similar patterns to for the Gray–Scott and Brusselator models.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, it is demonstrated that the nonuniform grids improve the accuracy of the solution considerably without any extra computational cost (see Table , Figure a,b). The present scheme offered better results than for the linear model, and similar patterns to for the Gray–Scott and Brusselator models.…”
Section: Resultssupporting
confidence: 71%
“…Some well‐known forms of this model, such as the Gray–Scott model, Brusselator model, Schnakenberg model, and prey–predator model have gained much attention from the research community due to their important applications to biology and chemistry. In this order, the Gray–Scott model has been analyzed and solved by several methods , as is the case with the Brusselator model , Schnakenberg model and prey–predator model .…”
Section: Introductionmentioning
confidence: 99%
“…All the computations are performed with N = 100 and the DG scheme with third-order accuracy. In Table 1, L ∞ -norms are estimated for the u variable, and the computed results are compared against the existing numerical results [61][62][63]. In addition, a profile comparison between the exact and numerical solutions for u and v at t = 1 is illustrated in Figure 2.…”
Section: Accuracy Test For Solvermentioning
confidence: 99%
“…All the computations are done with N = 100 and the DG scheme with third-order of accuracy. In Table 1, L ∞ -norms are estimated for the u variable, and the computed results are compared against the existing numerical results [60,61,62]. Also, a profile comparison between the true and numerical solutions for u and v at t = 1 is illustrated in Fig.…”
Section: One-dimensional Linear Rd Systemmentioning
confidence: 99%